Evaluation of culturing and molecular assay for detection of Mycoplasma gallisepticum in chicken suffering from chronic respiratory disease: Mycoplasma gallisepticum in chicken with chronic respiratory disease - Hamzah, Dhiaa J.; Ayed , Mdiha; Muhammed, Hayder A. (Cellular and Molecular Biology, 2022)
Mycoplasma gallisepticum (M. gallisepticum) is a bacterium that causes chronic respiratory disease (CRD) and infectious sinusitis (IS) in chicken and turkeys .Therefore, rapid and immediate diagnosis or regular detection of Mycoplasma may be of great help to early detection. 120 chicken layers, Within Karbala city was carried out during their laying period on breeding flocks. The study proposed a promising method for isolation of M. gallisepticum, 120 tracheal swabs and blood samples from chicken in different dairy farms were used to analyze M. gallisepticum utility of PCR and culture. Compared with ELISA anti-IgG M. gallisepticum, the clinical specificity of PCR detection is 89.66%, the sensitivity is 86.36%, and the kappa coefficient is 0.817. Compared with the culture method, the specificity is 100%, the specificity is 45%, and the kappa coefficient is 0.543. Demonstrate the method’s effectiveness and applicability as a standard method for mycoplasmas field diagnosis.